1998
DOI: 10.1152/ajpendo.1998.274.4.e692
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulation of glucose uptake in skeletal muscles and adipose tissues in vivo is NO dependent

Abstract: The purpose of this study was to investigate whether in vivo nitric oxide synthase (NOS) inhibition influences insulin-mediated glucose disposal in rat peripheral tissues. The NOS inhibitor N G-nitro-l-arginine methyl ester (l-NAME) or saline was infused constantly during a hyperinsulinemic-euglycemic clamp in normal rats. Glucose utilization rates of insulin-sensitive tissues (individual muscles, heart, and adipose tissues) were simultaneously determined using tracer infusion of 2-deoxy-d-[3H]glucose (2-[3H]D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
181
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(191 citation statements)
references
References 23 publications
10
181
0
Order By: Relevance
“…Studies with animals and humans supported the hypothesis that the glucose uptake pathway stimulated by NO may be independent of both insulin and muscle contraction (Higaki et al 2001, Henstridge et al 2009). However, other evidence have shown the importance of proper functioning of this system to optimize the insulin-dependent uptake of glucose (Roy et al 1998). In humans, inhibition of NO by L-NMMMA decreased glucose uptake in type 2 diabetics and healthy patients without affecting total blood flow (Bradley et al 1999).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…Studies with animals and humans supported the hypothesis that the glucose uptake pathway stimulated by NO may be independent of both insulin and muscle contraction (Higaki et al 2001, Henstridge et al 2009). However, other evidence have shown the importance of proper functioning of this system to optimize the insulin-dependent uptake of glucose (Roy et al 1998). In humans, inhibition of NO by L-NMMMA decreased glucose uptake in type 2 diabetics and healthy patients without affecting total blood flow (Bradley et al 1999).…”
Section: Nitric Oxide (No)mentioning
confidence: 99%
“…Whereas one report suggests that eNOS is also expressed in muscle cells [27], most studies failed to detect eNOS in these cells by immunocytochemistry [25,35,36], thus suggesting that the impaired eNOS expression in diabetic rats is mainly localised to the endothelial cells of the muscle vasculature. Because vascular NO production is important for the stimulatory action of insulin on skeletal muscle glucose uptake in vivo [17], the present data suggest that impaired muscle NOS activity is responsible, at least in part, for the lack of insulin-mediated glucose disposal in skeletal muscle of diabetic rats [5].…”
Section: Discussionmentioning
confidence: 64%
“…Nitric oxide synthase activity was quantified by the conversion of [ 3 H]-l-arginine to [ 3 H]-l-citrulline, with minor modifications [12,17]. Briefly, aliquots of the homogenates (100±200 mg proteins) were incubated in 50 mmol/l HEPES (pH 7.4) with 24 mmol/l [ 3 H]-l-arginine (0.1 mCi/tube), 120 mmol/l NADPH, 60 mmol/l l-valine, 12 mmol/l l-citrulline, 1.2 mmol/l MgCl 2 , 0.2 mmol/l CaCl 2 , 10 mg/ml calmodulin, 3 mmol/l BH4, 1 mmol/l flavin adenine dinucleotide (FAD) and 1 mmol/l flavin mononucleotide (FMN).…”
Section: Skeletal Muscle Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…5,13,14,50 It has been suggested that hyperuricemia inhibits nitric oxide availability and decreases insulin-mediated glucose uptake in skeletal muscle and may, therefore, have a role in the development of the metabolic syndrome. 51,52 Other studies have suggested that hyperinsulinemia, a consequence of the metabolic syndrome, enhances the tubular reabsorption of uric acid and that this occurs concurrently with a decrease in sodium and potassium excretion, leading to elevated BP. 53 In both instances, the association between abdominal obesity and high BP is mediated by hyperinsulinemia, 16 which is consistent with the notion of a common exposure to hyperinsulinemia (and obesity) in the relation between SUA and BP.…”
Section: Discussionmentioning
confidence: 99%